Hybrid use of combined and sequential delivery of growth factors and ultrasound stimulation in porous multilayer composite scaffolds to promote both vascularization and bone formation in bone tissue engineering. Issue 1 (27th August 2015) - Yan, Haoran; Liu, Xia; Zhu, Minghua; Luo, Guilin; Sun, Tao; Peng, Qiang; Zeng, Yi; Chen, Taijun; Wang, Yingying; Liu, Keliang; Feng, Bo; Weng, Jie; et al.
Abstract: In this study, a multilayer coating technology would be adopted to prepare a porous composite scaffold and the growth factor release and ultrasound techniques were introduced into bone tissue engineering to finally solve the problems of vascularization and bone formation in the scaffold whilst the designed multilayer composite with gradient degradation characteristics in the space was used to match the new bone growth process better. The results of animal experiments showed that the use of low intensity pulsed ultrasound (LIPUS) combined with growth factors demonstrated excellent capabilities and advantages in both vascularization and new bone formation in bone tissue engineering. The degradation of the used scaffold materials could match new bone formation very well. The results also showed that only RGD‐promoted cell adhesion was insufficient to satisfy the needs of new bone formation while growth factors and LIPUS stimulation were the key factors in new bone formation. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 195–208, 2016.